Zapomniane uczone Uniwersytetu Poznańskiego: doc. dr hab. Wisława Knapowska – nauczycielka i historyczka (7.06.1889-8.05.1956) - Głowacka-Sobiech, Edyta (Wydawnictwo Naukowe UAM, 2018)
The text introduces the figureof Wisława Knapowska, one of the firstindependent scholars of Poznań University, a researcher and teacher of the best schools in the interwar period. It shows her path to academic independence and the many barriers she encountered in her life. The text is part of the socalled herstory, asking for the past and history of women’s narratives.
Forgotten Female Scholars of Poznań University – Prof. Wisława Knapowska – Teacher and Historian (7.06.1889-8.05.1956)
Keywords: herstory; history; didactics; interwar period; emancipation